HBR's 10 Must Reads on Business Model Innovation - Review, Harvard; Christensen, Clayton; Johnson, Mark; McGrath, Rita; Blank, Steve (Ascent Audio, 2021)
Rethink how your organization creates, delivers, and captures value-or risk becoming irrelevant. If you listen to nothing else on business model innovation, listen to these ten articles. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you reach new customers and stay ahead of your competitors by reinventing your business model. This book will inspire you to: assess whether your core business model is going strong or running out of gas; fend off free and discount entrants to your market; reinvigorate growth by adding a second business model; adopt the practices of lean startups; develop a platform around your key products; and make business model innovation an ongoing discipline within your organization.